A végzet városa: A debreceniség emlékezete Szabó Magda Kiálts, város! című drámájában - Baranyai, Norbert (Studia Litteraria, 2021)
The study analyzes Magda Szabó’s historical drama “Shout, City!” looking for an answer to how the memory of Debrecen appears in the play. In the first two chapters, the paratexts of the play (title, prologue) are examined, followed by an analysis of the characteristics of the memory in the drama. The drama recalls different memorial topoi associated with Debrecen, reflecting that these are constructed by literary tradition. Magda Szabó’s text not only simply evokes the memorial narratives of Debrecen, but also questions their validity due to the dramatic events and the rhetorical complexity of the dramatic language. One chapter of the study discusses in detail the dramatic memory and dramaturgical role of Calvinian predestination. The analysis concludes that “Shout, City!” evokes Calvinist thoughts and their memorial narratives through a complex dialogue, shaped by dramatic events, dialogues and debates between characters. e nal chapter examines the end of the drama, based on Aleida Assmann’s study, focusing primarily on the issue of sacrice. As a result, the signicance of Magda Szabó’s historical drama is not given by drama poetic innovation, but by the intention to rethink the stories that construct the cultural memory of Debrecen.